An analysis of undergraduate students’ higher order thinking skills in Geometry - Safrida, L N; Susanto; Setiawan, T B; Ambarwati, R; Hussen, S (Journal of physics. Conference series, 2021)
Higher order thinking skill (HOTS) becomes important thing and issue in teaching and learning, especially in Mathematics. By using HOTS, students could solve the complicated problems and situation that could be used in real life. So that, the students could be ready to encounter high technology developing and industry revolution 4.0. Then, students could compete with foreign students. The purpose of this study is to describe the higher order thinking skills’ students in proving geometry theorem. This study uses qualitative research and conducted to the undergraduate students. The result of this study shows that the highest HOTS score equal to 80 and the lowest HOTS score equal to 30, then the average of HOTS score is 62. The subjects with low score, only try to analyse the statement without clear reason. The subjects with medium score begin to analyse and evaluate the problem with reason although it’s not clear enough. The subjects with high score begin to create new idea in proving theorem although sometimes could explain the reason. At the end, they could draw the conclusions based on the problems.